A Comparative Effectiveness Systematic Review and Meta-analysis of Drugs for the Prophylaxis of Junctional Ectopic Tachycardia - Mendel, Brian; Christianto, Christianto; Setiawan, Moira; Prakoso, Radityo; Siagian, Sisca N. (Current Cardiology Reviews, 2022)
Background: Junctional Ectopic Tachycardia (JET) is an arrhythmia originating from the AV junction, which may occur following congenital heart surgery, especially when the intervention is near the atrioventricular junction. Objective: The aim of this systematic review and meta-analysis is to compare the effectiveness of amiodarone, dexmedetomidine, and magnesium in preventing JET following congenital heart surgery. Methods: This meta-analysis was conducted according to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement, where 11 electronic databases were searched from the date of inception to August 2020. The incidence of JET was calculated with the relative risk of 95% Confidence Interval (CI). Quality assessment of the included studies was assessed using the Consolidated Standards of Reporting Trials (CONSORT) 2010 statement. Results: Eleven studies met the predetermined inclusion criteria and were included in this meta-analysis. Amiodarone, dexmedetomidine, and magnesium significantly reduced the incidence of postoperative JET [Amiodarone: risk ratio 0.34; I2= 0%; Z=3.66 (P=0.0002); 95% CI 0.19-0.60. Dexmedetomidine: risk ratio 0.34; I2= 0%; Z=4.77 (P<0.00001); 95% CI 0.21-0.52. Magnesium: risk ratio 0.50; I2= 24%; Z=5.08 (P<0.00001); 95% CI 0.39-0.66]. Conclusion: All three drugs have shown promising results in reducing the incidence of JET. Our systematic review found that dexmedetomidine is better in reducing the length of ICU stays as well as mortality. In addition, dexmedetomidine also has the least pronounced side effects among the three. However, it should be noted that this conclusion was derived from studies with small sample sizes. Therefore, dexmedetomidine may be considered as the drug of choice for preventing JET.
Keywords: Amiodarone